2010
DOI: 10.1038/jp.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pneumonia with sepsis caused by intrauterine infection of Ureaplasma parvum in a term newborn: a first case report

Abstract: We present an autopsy case of intrauterine pneumonia in a term newborn in whom Ureaplasma parvum was confirmed by PCR examinations, including a novel diagnostic tool for detecting pathogens that caused neonatal infections using multiplex PCR. This is the first report of U. parvum being implicated in the pathogenesis of congenital pneumonia with sepsis in a term newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…can result in chorioamnionitis, dissemination to fetal organs, and congenital pneumonia with sepsis. These consequences of the intrauterine Ureaplasma infection can be observed even in newborns [3,8,24].…”
Section: Immunologymentioning
confidence: 94%
“…can result in chorioamnionitis, dissemination to fetal organs, and congenital pneumonia with sepsis. These consequences of the intrauterine Ureaplasma infection can be observed even in newborns [3,8,24].…”
Section: Immunologymentioning
confidence: 94%
“…Strains classified as biovar 1 were designated as a separate species, Ureaplasma parvum , whereas strains with biovar 2 traits retained the U. urealyticum designation 12,13 . Recently, it has been reported that intrauterine infection of U. parvum can cause congenital pneumonia and sepsis even in term newborns 14 . New studies suggest that U. urealyticum and U. parvum may be an important cause of lung injury in newborns and neonates through a number of mechanisms including the inhibition of pulmonary surfactant as well as the production of IL and soluble intercellular adhesion molecules 15 .…”
Section: Introductionmentioning
confidence: 99%
“…(18). Pneumonia caused by Ureaplasma species, Eubacteria mainly colonizing the mucosal surface of the respiratory and urogenital tract, may be diagnosed by direct isolation of the organism from endotracheal aspirates using culture or PCR-techniques, by typical chest-x-ray patterns showing disseminated, patchy infiltrates bilaterally with progression to cystic dysplasia, and elevated inflammatory serum-parameters like CRP or an increased white cell count (19,20,21). An organism frequently associated with early onset pneumonia is Group B Streptococcus.…”
Section: Diagnosismentioning
confidence: 99%